Nanda Devi 1980 : in pursuit of adventure - Jasjit Mansingh, 1938- (Sapper Adventure Foundation, 1981)
On the 1980 Sapper Expedition to Nanda Devi, mountain in Kumaun Himalayas by a team from the Corps of Engineers.